Progress in understanding the relationship between long noncoding RNA and endometriosis. (January 2020) - Yan, Wenying; Hu, Hongmei; Tang, Biao
Abstract: Endometriosis is a common gynecological disease. However, the etiology of endometriosis is still unclear, and current theories cannot fully elaborate its specific pathogenesis. Recently, some research has suggested that the occurrence and development of endometriosis may be related to genetics. Long-chain non-coding RNA (lncRNAs) is a kind of non-protein-coding RNA molecule with a length of 200-100, 000 bp. With complex biological functions, lncRNAs play an important role in the normal development of individuals and the progression of various diseases, and lncRNAs have become an important field of medical research in recent years. This paper mainly illustrates the research progress on lncRNAs as they relate to endometriosis. We also provide some ideas for exploring the pathogenesis of endometriosis.